2000
DOI: 10.1109/20.908674
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-current-induced domain wall propagation in Permalloy patterns observed using magnetic force microscope

Abstract: Abstract-Pulsed-current controlled wall motion in 20 m wide 200 m long 160 nm thick patterned Permalloy strips was studied using magnetic force microscopy. By sequential imaging, the displacement of Bloch walls as far as 200 m along the strip was observed. The direction of motion was in the same direction as the carrier velocity, which reversed with current polarity. The displacement per pulse was dependent upon the sample thickness and current density, which suggests that the mechanism is a combination of s-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…For the constriction width of 500 nm, this dc offset corresponds to a current density of $10 11 A=m 2 . This behavior is not symmetrical with reversal of current direction, confirming that the suppression of DW pinning is due to the spin-polarized current acting on the wall, which augments the effect of the field [2,15]. We can rule out the Joule heating effect as the cause of DW pinning suppression since that effect is independent of the current direction.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…For the constriction width of 500 nm, this dc offset corresponds to a current density of $10 11 A=m 2 . This behavior is not symmetrical with reversal of current direction, confirming that the suppression of DW pinning is due to the spin-polarized current acting on the wall, which augments the effect of the field [2,15]. We can rule out the Joule heating effect as the cause of DW pinning suppression since that effect is independent of the current direction.…”
mentioning
confidence: 71%
“…Experimental work on this subject includes studies on ferromagnetic thin films [2,3], nanowires [4][5][6][7][8], and wires with patterned pinning sites [9][10][11][12][13]. In addition to the early theoretical work [14,15], recent reformulations have been proposed, based on a microscopic approach [16][17][18][19].…”
mentioning
confidence: 99%
“…In this paper, we focus our discussions on two effects: domain wall dynamics and magnetization instability. Recently, both topics have received considerably interests in experiments [1,2,3,4,5,6,7,8,9,10,11] and in theories [12,13,14,15,16,17,18,19]. It is shown that the current is able to displace magnetic domain walls in a spin valve [3], in a constricted nanowire [4], in U-shaped (or L-shaped) nanowires [5,6], in a ring structure [7] and in zigzag wires [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The experimentally observed consequences include domain wall ͑DW͒ motion, [3][4][5][6][7][8] depinning, [9][10][11][12] resonance, [13][14][15][16] and transformation. 17 This effect has applications in solid state storage class memories 18 and is the basis for a magnetic logic gate design.…”
Section: Spin-transfer Torque Efficiency Measured Using a Permalloy Nmentioning
confidence: 99%